Diagnostic Techniques in Industrial Engineering - Ram, Mangey; Davim, J. Paulo (Cham : Springer International Publishing, 2018)
This book presents the most important tools, techniques, strategy and diagnostic methods used in industrial engineering. The current widely accepted methods of diagnosis and their properties are discussed. Also, the possible fruitful areas for further research in the field are identified.
Includes bibliographical references and index.
Keywords: Industrial engineering; Mechanical engineering; Automatic control; Production engineering